Alterations in intestinal microbiota and enzyme activities under cold-humid stress: implications for diarrhea in cold-dampness trapped spleen syndrome - Wu, Yi; Deng, Na; Liu, Jing; Jiang, Ping; Tan, Zhoujin (Frontiers in Microbiology, 2023)
Cold and humid environments alter the intestinal microbiota, and the role of the intestinal microbiota in the development of diarrhea associated with cold-dampness trapped spleen syndrome in Chinese medicine is unclear. We randomly divided 30 mice into normal and model groups, and the model group were exposed to cold and humid environmental stresses for 7 days. Then, mouse intestinal contents were collected and analyzed their intestinal microbiota and digestive enzymes. Our findings revealed significant increases in sucrase and lactase activities, as well as microbial activity, in the model group (P < 0.05). β-diversity analysis highlighted distinct intestinal microbiota compositions between the two groups. Specifically, the experimental group showed a unique dominance of the genera and strains Clostridium sensu stricto 1 and Clostridium sp. ND2. LEfSe analysis identified Helicobacter, Roseburia, and Eubacterium plexicaudatum ASF492 as differentially abundant species in them model group. Network analysis demonstrated that rare bacterial species mostly governed the microbial interactions, exhibiting increased mutual promotion. On the other hand, abundant species like Lactobacillus johnsonii and Lactobacillus reuteri showed mutual inhibitory relationships. In summary, exposure to cold and humid conditions led to increased intestinal enzyme activities and a shift in microbial composition, favoring the growth of rare bacterial species. These changes suggest that rare bacteria in the intestinal microbiota play a critical role in the pathology of diarrhea associated with cold-dampness trapped spleen syndrome, revealing unique survival strategies among bacterial populations under stressful conditions.